Knowledge and practices of private healthcare providers regarding tuberculosis case notification in Rural Maharashtra - Holkar, Mrudula; Krishna, Swathi; Shah, Rohan; Pawar, Radhakishan; Juvekar, Sanjay (Intelektual Pustaka Media Utama, 2024)
India carries the highest share of active and missing tuberculosis (TB) cases globally. The Government of India is prioritizing private sector engagement (PSE) in TB elimination activities, as most healthcare-seeking in the country happens in this sector. This study aimed to understand the knowledge and practices of private healthcare providers (PHP) on various aspects of TB case notification through the National TB Elimination Programme (NTEP). This cross-sectional study was carried out between Oct 2020 to April 2021 amongst PHPs in the Junnar Tuberculosis Unit (TU), Pune District, Maharashtra. Junnar Block has 299 PHPs who assess, diagnose, and/or treat TB cases. A total of 97 participants were enrolled in the study. About 89 (91.8%) PHPs are aware that TB case notifications are mandatory by law. However, 80.4% are unaware of the Ni-kshay portal (web-based case surveillance system) by NTEP. Similarly, 74 (76.3%) must be aware of incentives for PHPs to collaborate with the government healthcare delivery system. 82.8% of total Ayurveda, Unani, Naturopathy, Siddha, and Homeopathy (AYUSH) practitioners and 46.2% of Allopathic practitioners have poor knowledge about TB case notification, with a Chi-square value of 14.36 (p<0.01). Our study shows that the active engagement of private providers (PPs), especially AYUSH practitioners in rural areas, is a need of the hour in achieving TB elimination.